2021
DOI: 10.1001/jamacardio.2021.1106
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Left Ventricular Systolic Dysfunction Among Carriers of Truncating Variants in Filamin C With Frequent Ventricular Arrhythmia and End-stage Heart Failure

Abstract: IMPORTANCETruncating variants in the gene encoding filamin C (FLNCtv) are associated with arrhythmogenic and dilated cardiomyopathies with a reportedly high risk of ventricular arrhythmia.OBJECTIVE To determine the frequency of and risk factors associated with adverse events among FLNCtv carriers compared with individuals carrying TTN truncating variants (TTNtv). DESIGN, SETTING, AND PARTICIPANTSThis cohort study recruited 167 consecutive FLNCtv carriers and a control cohort of 244 patients with TTNtv matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…These studies have broadly found that cardiomyopathy in individuals with FLNCLOF is characterized by LV dysfunction/dilation, a high burden of malignant arrhythmia/sudden cardiac arrest, frequent findings of myocardial fibrosis, and reported high rates of penetrance. 2,3,6,10,26,27 Despite the stark differences in clinical context, the characteristics of this genome-first cohort generally recapitulate these findings. For example, FLNCLOF variants were associated with LV dilatation (increased LVIDd) and decreased LVEF, with 25% of carriers being classified as having ventricular dysfunction from EHR-based phenotypes (18% via chart review).…”
Section: Phenotype Characteristics Of Flnclof Through Genome-first Approachmentioning
confidence: 55%
See 3 more Smart Citations
“…These studies have broadly found that cardiomyopathy in individuals with FLNCLOF is characterized by LV dysfunction/dilation, a high burden of malignant arrhythmia/sudden cardiac arrest, frequent findings of myocardial fibrosis, and reported high rates of penetrance. 2,3,6,10,26,27 Despite the stark differences in clinical context, the characteristics of this genome-first cohort generally recapitulate these findings. For example, FLNCLOF variants were associated with LV dilatation (increased LVIDd) and decreased LVEF, with 25% of carriers being classified as having ventricular dysfunction from EHR-based phenotypes (18% via chart review).…”
Section: Phenotype Characteristics Of Flnclof Through Genome-first Approachmentioning
confidence: 55%
“…A total of 171,948 MyCode participants had available sequencing data linked to their EHR. Of these, 60 individuals (0.03%) were identified harboring 27 unique FLNCLOF variants, comprising frameshift (n=14), splice site (10), and stop gained (3). Variant details are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with DSP mutations can be presented with typical ARVC, biventricular cardiomyopathy, or isolated LV, as well as DCM ( 19 ). Recent research have found that truncating variants in the gene-encoding filamin C ( FLNCtv ) are associated with arrhythmogenesis and DCM, with a reportedly high risk of ventricular arrhythmia ( 20 ). In addition, many genes have been identified in ARVC and are listed as pathogenic genes in DCM, such as PKP2, JUP, LMNA, DES, PLN , and SCN5A ( 1 , 21 ).…”
Section: Discussionmentioning
confidence: 99%